A new clustering method identifies multiple sclerosis‐specific T‐cell receptors. Issue 1 (5th January 2021) - Hayashi, Fumie; Isobe, Noriko; Glanville, Jacob; Matsushita, Takuya; Maimaitijiang, Guzailiayi; Fukumoto, Shoko; Watanabe, Mitsuru; Masaki, Katsuhisa; Kira, Jun‐ichi
Abstract: Objective: To characterize T‐cell receptors (TCRs) and identify target epitopes in multiple sclerosis (MS). Methods: Peripheral blood mononuclear cells were obtained from 39 MS patients and 19 healthy controls (HCs). TCR repertoires for α/β/δ/γ chains, TCR diversity, and V/J usage were determined by next‐generation sequencing. TCR β chain repertoires were compared with affectation status using a novel clustering method, Grouping of Lymphocyte Interactions by Paratope Hotspots (GLIPH). Cytomegalovirus (CMV)‐IgG was measured in an additional 113 MS patients and 93 HCs. Regulatory T cells (Tregs) were measured by flow cytometry. Results: TCR diversity for all four chains decreased with age. TCRα and TCRβ diversity was higher in MS patients ( P = 0.0015 and 0.024, respectively), even after age correction. TRAJ56 and TRBV4‐3 were more prevalent in MS patients than in HCs ( p corr = 0.027 and 0.040, respectively). GLIPH consolidated 208, 674 TCR clones from MS patients into 1, 294 clusters, among which two candidate clusters were identified. The TRBV4‐3 cluster was shared by HLA‐DRB1*04:05 ‐positive patients (87.5%) and predicted to recognize CMV peptides (CMV‐TCR). MS Severity Score (MSSS) was lower in patients with CMV‐TCR than in those without ( P = 0.037). CMV‐IgG‐positivity was associated with lower MSSS in HLA‐DRB1*04:05 carriers ( P = 0.0053). HLA‐DRB1*04:05 ‐positive individuals demonstrated higher CMV‐IgG titers than HLA‐DRB1*04:05 ‐negative individuals ( P = 0.017). CMV‐IgG‐positive patients had more Tregs than CMV‐IgG‐negative patients ( P = 0.054). Interpretation: High TCRα/TCRβ diversity, regardless of age, is characteristic of MS. Association of a CMV‐recognizing TCR with mild disability indicates CMV's protective role in HLA‐DRB1*04:05 ‐positive MS.